Identification of a CE-SDS shoulder peak as disulfide-linked fragments from common CH2 cleavages in IgGs and IgG-like bispecific antibodies. Issue 1 (1st January 2021) - Cao, Mingyan; Jiao, Yang; Parthemore, Conner; Korman, Samuel; Ma, Jiao; Hunter, Alan; Kilby, Greg; Chen, Xiaoyu
ABSTRACT: Fragmentation is a well-characterized degradation pathway of therapeutic antibodies and is usually monitored by capillary electrophoresis–sodium dodecyl sulfate (CE-SDS). Although fragments due to cleavage in CH 2 domains linked by intrachain disulfide bonds are common and can be detected by reduced reversed-phase – liquid chromatography mass spectrometry (RP-LCMS) and reduced CE-SDS methods, their separation in nonreduced CE-SDS (nrCE-SDS) has not been reported but speculated as comigrating with intact IgG. A shoulder peak in nrCE-SDS was observed in the stability samples of an IgG-like bispecific antibody and was determined to be mainly caused by fragments from clipping at the C-terminus of leucine (L)306 or L309 (EU numbering) in the CH 2 domain of both heavy chains (HCs) and, to a lesser degree, at the C-terminus of L182 in the CH 1 domain of the knob HC. Subunit LCMS analysis verified that the crystallizable fragment contained variants with one or multiple mass additions of ~18 Da due to clipping. Further investigation revealed that CH 2 clippings at L306 and L309 were largely due to proteolytic activity, and cleavages were present at various levels in all in-house IgG1 and IgG4 molecules studied. Our study shows that CH 2 domain cleavages, with complementary fragments still linked by intrachain disulfide, can be electrophoretically resolved as a front shoulder of the main peak in nrCE-SDS. Given the high occurrence of CH 2 cleavages in antibodies, these findings will have broad applicability and could help manufacturers of therapeutic antibodies in process improvement, product characterization, investigations, formulation stability, and stability comparability studies.